The Way to Happiness, Understanding and Peace - Compton, Wilson Martindale (Tufts Archival Research Center, 2006)
Wilson Compton describes the influence of his Presbyterian parents on his beliefs (including his mother's child-rearing philosophy of "The Bible, soap, and spinach"), and he explains how the Golden Rule is a concept found in all of the major world religions.